Small Intestinal Strangulation Secondary to Omental Adhesion Entrapment in a Dog - Alexandra Garrett; Hayley Gallaher; Maureen Spinner (Case Reports in Veterinary Medicine)
A 6-year-old, male neutered, German Shorthaired Pointer was evaluated for acute onset of emesis, tenesmus, and restlessness. Abdominal radiographs suggested gastrointestinal obstruction or torsion. An exploratory laparotomy revealed an omental-to-mesenteric adhesion causing entrapment and strangulation of a segment of the jejunum, along with several other adhesions. The patient had undergone two previous laparotomies, which likely contributed to the extensive adhesion formation found intraoperatively. While postsurgical adhesion formation is a known complication in both human and veterinary medicine, this case is notable for the unusual origin of the adhesions arising from the omentum. Furthermore, the severity of strangulation resulting from this adhesion required more extensive surgery and posed a higher risk for long-term gastrointestinal complications, such as short bowel syndrome.